A Case Report Of A Very Rare Mixed Ovarian Tumour (Journal of Pharmaceutical Negative Results, 2022)
A 30yr old female unmarried came to OPD with the complaints of lower abdominal pain for past 1 week. on systemic examination P/A : Soft, A cystic mass of size 5*4cm felt in left illiac fossa, mobile , mild tenderness present .L/E : Hymen intact P/R : Rectal mucosa free and same mass felt .Tumour markers are Ca125 12.73, AFP 2.27 and LDH 169.On CT abdomen and pelvis(plain) Uterus and right ovary normal.There is a evidence of well-defined ellipsoid multilocated cystic lesion measuring 7.95 (AP)* 11.5(TR)*9.3(CC) cm seen arising from left ovary occupying right adenexa and anterior placed to uterus . Impression : Left ovarian mass. Macro findings complex ovarian cystic tumour. Pathological discussion Multiple sections studied from from the solid and cystic areas of ovarian tumour shows tubular glands Impression: Suggestive of clear cells + mucinous cyst adenofibroma of borderline tumour – mixed cell type .